Faktor-faktor yang mempengaruhi keberkesanan penilaian prestasi guru besar Sekolah Rendah di Bahagian Sarikei, Sarawak - Sinyap, Adline (2002)
The purpose of this study is to describe the performance appraisal efficiency level under the New Remuneration System (Sistem Saraan Baru) and the factors affecting the performance appraisal efficiency level among the Headmasters in the primary schools in Sarikei Division, Sarawak. The whole population was chosen for the study. The survey method was adopted for the study.